2010
DOI: 10.2111/rem-d-09-00106.1
|View full text |Cite
|
Sign up to set email alerts
|

Soil Carbon Pools in California’s Annual Grassland Ecosystems

Abstract: Rangeland ecosystems cover approximately one-third of the land area in the United States and half of the land area of California. This large land area, coupled with the propensity of grasses to allocate a considerable proportion of their photosynthate belowground, leads to high soil carbon (C) sequestration potential. Annual grasslands typical of the Mediterranean climates of the western United States differ in their life history strategies from the well-studied perennial grasslands of other regions and thus m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
41
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
2
1

Relationship

2
8

Authors

Journals

citations
Cited by 66 publications
(48 citation statements)
references
References 87 publications
5
41
0
Order By: Relevance
“…In California annual grasslands, soil C pools in the top meter average 140 Mg C ha -1 though the range in these pools span almost 200 Mg C ha -1 across sites, with higher values where woody vegetation is present (Silver et al 2010). Conversion of rangelands to cropland or urban lands can release large quantities of carbon (Lal 2002;Potthoff et al 2005;Chen et al 2013).…”
Section: Introductionmentioning
confidence: 99%
“…In California annual grasslands, soil C pools in the top meter average 140 Mg C ha -1 though the range in these pools span almost 200 Mg C ha -1 across sites, with higher values where woody vegetation is present (Silver et al 2010). Conversion of rangelands to cropland or urban lands can release large quantities of carbon (Lal 2002;Potthoff et al 2005;Chen et al 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Addition of organic input from cow dung may contribute to slight increment of organic matter in the grazing lands compared with cultivated lands (Mekuria et al, 2009;Haile et al, 2014;Mekuria et al, 2014), but overgrazing may cause degradation of soil organic matter compared with agroforestry systems (Haile et al, 2014). Many findings have shown that grasslands can fix organic carbon in the soil reaching up to 100 Mg C ha -1 ) (Silver et al, 2010). For instance, conversion of free grazing lands to area exclosures have shown potential of increasing carbon stocks in the area (Mekuria et al, 2009), and if continued, this strategy may contribute to achieve equilibrium state in carbon sequestration.…”
Section: Soils Of Grazing Landsmentioning
confidence: 99%
“…Despite the inherently low SOC sequestration rates that have been reported in grasslands when compared with other land uses, their global impact can be significant given the surface covered by this land use (Follett and Schuman 2005). The potential C storage in grasslands varies according to climatic conditions and management (Silver et al 2010). For instance, the last authors reported soil C contents of 200 Mg C ha −1 in the first 100-cm soil depth in annual grass-dominated rangelands in California.…”
Section: Livestock Integration Into Dryland Farming Systemsmentioning
confidence: 99%